Office for iPad and Mac for dummies - Weverka, Peter (John Wiley & Sons, 2015)
"Packed with easy-to-follow, step-by-step instructions, this friendly guide walks you through every facet of Office, from installing the software to working with Word, Excel, and PowerPoint -- and beyond. There's never been a better time to bring Office to your iPad or Mac, and this go-to reference makes it easier than ever."--
Print version record
Keywords: Microsoft Office; iPad (Computer); Macintosh (Computer); Integrated software; iPad (Ordinateur); Macintosh (Ordinateur); Logiciels intégrés